Resposta funcional da joaninha Cryptolaemus predando Cochonilha branca em diferentes temperaturas e substratos vegetais - Bortoli, Sergio Antonio de [UNESP]; Gravena, Adriana Rossini [UNESP]; Vacari, Alessandra Marieli [UNESP]; Laurentis, Valeria Lucas de [UNESP]; Bortoli, Caroline Placidi de [UNESP] (Universidade Federal Rural do Semi-Árido (UFERSA), 2014)
This work was carried out to evaluate the functional response of Cryptolaemus montrouzieri Mulsant, 1850 (Coleoptera: Coccinellidae) fed with Planococcus citri Risso, 1813 (Hemiptera: Pseudococcidae) reared on a pumpkin hybrid (Cucurbita maxima x Cucurbita moscata) (Cucurbitaceae), seedlings of Rangpur lime (Citrus limonia) Rutaceae) and potato (Solanum tuberosum) (Solanaceae) at two temperatures. The predation rate of C. montrouzieri was measured using Petri dishes of 15 cm diameter with 1, 2, 4, 8, 16 and 24 adults of P. Citri. One third instar larva, one fourfh instar and one newly emerged adult (without differentiation of sex) of C. montrouzieri were added to each plate. The study was conducted in climatic chambers at temperatures of 25 and 30 degrees C and photophase of 12 hours. The predation rate was evaluated after 24 hours of prey exposition to the predator, by counting the number of preys trapped in the different treatments and control. The statistical design was completely randomized with four treatments x 6 subplots with 7 repetitions, the two temperatures. The values obtained were subjected to analysis of variance, to relate the number of scales preyed by larvae and adults of C. montrouzieri set up in different substrates. The amount of prey consumed by larvae and adults of the predator increased with increasing the prey density until it reaches a plateau, characterizing functional response type II. In general, the number of scales preyed by larvae and adults of C. montrouzieri was higher on potato and under temperature of 30 degrees C.

O objetivo do trabalho foi avaliar a resposta funcional de Cryptolaemus montrouzieri Mulsant, 1850 (Coleoptera: Coccinellidae) alimentada com Planococcus citri Risso, 1813 (Hemiptera: Pseudococcidae) criada em abóbora cabotcha (Cucurbita maxima x Cucurbita moscata) (Cucurbitaceae), mudas de limão cravo (Citrus limonia) (Rutaceae) e batata (Solanum tuberosum) (Solanaceae). A taxa de predação de C. montrouzieri foi medida utilizando-se 1, 2, 4, 8, 16 e 24 adultos de P. citri em placas de Petri (15 cm de diâmetro) contendo uma larva de terceiro estádio, uma de quarto estádio e um adulto recém emergido e sem distinção de sexo. O estudo foi conduzido em câmaras climatizadas com temperaturas de 25 e 30ºC e fotofase de 12 horas. A taxa de predação foi avaliada com 24 horas de exposição do predador à presa, verificando-se o número de presas presentes nos diferentes tratamentos e no controle. O delineamento estatístico adotado foi o inteiramente casualizado, com 4 tratamentos x 6 subparcelas com 7 repetições, nas duas temperaturas estudadas. Os valores obtidos foram submetidos a análise de variância, visando comparar o número de cochonilhas predadas pelas larvas e adulto da joaninha criadas nos diferentes substratos. Tanto para as larvas quanto para os adultos de C. montrouzieri, a quantidade de adultos de P. citri predados aumentou com o incremento da densidade da presa até atingir um platô (resposta funcional do Tipo II). De forma geral o número de cochonilhas predadas pelas larvas e adultos de C. montrouzieri foi maior quando esse predador desenvolveu-se sobre os talos de batata e na temperatura de 30°C.
Functional response of mealybug destroyer preyng citrus mealybug under different temperatures and vegetable substrates
Keywords: Cryptolaemus montrouzieri; Planococcus citri; Pumpkin hybrid; Rangpur lime; Potato; Cryptolaemus montrouzieri; Planococcus citri; Batata; Abóbora; Citros